ФІЗИЧНА КУЛЬТУРА В ПОЗААУДИТОРНІЙ ДІЯЛЬНОСТІ ЯК ФОРМУЮЧА ЗДОРОВОГО ОБРАЗУ ЖИТТЯ МОЛОДІ (Педагогіка вищої та середньої школи, 2002)
In the article author analyses the different forms of physical culture in the past and the present. The author notes that physicalculture of nowadays must formulate the style of the modern student, learn him to support the necessary state of health.